Pharmacotranscriptomic Biomarkers in Glucocorticoid Treatment of Pediatric Inflammatory Bowel Disease - Lucafò, Marianna; Stankovic, Biljana; Kotur, Nikola; Di Silvestre, Alessia; Martelossi, Stefano; Ventura, Alessandro; Zukic, Branka; Pavlovic, Sonja; Decorti, Giuliana (Current Medicinal Chemistry, 2018)
Background: Pharmacotranscriptomics aims to reach more accurate drug dosing based on interindividual transcriptome variations. Here, we provide an overview of RNA biomarkers that could predict the response to glucocorticoids (GCs), considered the standard for treatment of inflammatory bowel diseases (IBD), both in adult and pediatric patients. Although new biological agents are very effective in IBD treatment, GCs are still widely used for induction of remission in patients with moderate to severe disease. It is important to identify patients that are poor responders to GCs therapy, because suboptimal response is frequent and associated with various side effects. A number of genetic variants related to GC mechanism of action has been studied. However, the majority of reported associations are not consistent. In this regard, pharmacogenomic research is now exploring the world of RNAs. An appropriate regulation of the transcriptome, which mainly comprises mRNAs and non-coding RNAs that control gene expression, has a strong impact in the modulation of GC activity. Aim: The aim of this review is to present the current knowledge of the role of the transcriptome in modulating GC response in pediatric IBD. Results: We will discuss the available literature, concerning the development of pharmacotranscriptomic biomarkers, focusing particularly on non-coding RNAs, and present the results in this field that elucidate a concrete benefit of translating the knowledge gained in the
Keywords: Glucocorticoids